(untitled) (Innovative professional education, 2024)
The article offers examples of the development of educational cases in the process of training future skilled workers. The introduction of educational cases into the educational process will contribute to the assimilation of modern European labor safety standards, will form a healthy environment for Ukrainian business of all forms of ownership.